2014
DOI: 10.1021/am506585u
|View full text |Cite
|
Sign up to set email alerts
|

Photocurrent Enhancement of BODIPY-Based Solution-Processed Small-Molecule Solar Cells by Dimerization via the Meso Position

Abstract: Three 4,4-difluoro-4-bora-3a,4a-diaza-s-indancene (BODIPY)-based small molecule donors H-T-BO, Br-T-BO, and DIMER were synthesized and fully characterized. Although modification at the meso position has a subtle influence on the light-harvesting ability, energy levels, and phase sizes, it has a striking effect on the packing behavior in solid film as two-dimension grazing incidence X-ray diffraction (2D GIXRD) and X-ray diffraction (XRD) confirm. Br-T-BO exhibits better packing ordering than H-T-BO in pristine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 50 publications
0
42
0
Order By: Relevance
“…138−141 Yao et al reported three BODIPY-based near-IR small molecules, S18, S19, and S20 ( Figure 19). 142 All of these small molecules show broad absorption bands with onset absorption extending to 880−900 nm. They found that S19 tends to pack in a more ordered way than S18 in the pristine film, which might benefit from the intermolecular interaction from the halogen bond.…”
Section: Low-bandgap Small Molecules Based On Bodipymentioning
confidence: 99%
“…138−141 Yao et al reported three BODIPY-based near-IR small molecules, S18, S19, and S20 ( Figure 19). 142 All of these small molecules show broad absorption bands with onset absorption extending to 880−900 nm. They found that S19 tends to pack in a more ordered way than S18 in the pristine film, which might benefit from the intermolecular interaction from the halogen bond.…”
Section: Low-bandgap Small Molecules Based On Bodipymentioning
confidence: 99%
“…Liu et al. synthesized and fully characterized three new BODIPY‐based small molecular donors 15 – 17 (Figure ) . Modification at the meso ‐position showed slight influence on the light‐harvesting ability, energy levels, and domain sizes, but it was very effective in tuning the packing behavior in the solid state.…”
Section: Introductionmentioning
confidence: 99%
“… UV‐vis absorption spectra of the three donors in the blend films (dashed lines) (1 : 2 for 15 (H‐T‐BO) : PC 71 BM and 1 : 2.5 for 16(Br‐T‐BO) : PC 71 BM and 17(DIMER) : PC 71 BM, w/w) . The absorption spectra (solid lines) for the neat films are also displayed for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the popular electron-rich units contain benzodithiophene (BDT), 1-5 dithienosilole, 6-8 oligthiophene, [9][10][11] triarylamine, 12-14 phenyl-1,3,5-trithiophene derivative, 15 porphyrin, 16,17 etc. Diketopyrrolopyrrole (DPP), [18][19][20] isoindigo (ID), 21,22 benzothiadiazole (BT), 23,24 thiazole, 25 dipyrromethene boron difluoride (BODIPY), [26][27][28] etc. are used as the electron-deficient units.…”
Section: Introductionmentioning
confidence: 99%
“…6 Interestingly, the two α-positions π-extending BODIPY-donor film shows the onset absorption beyond 900 nm. 28 4,8-bis (2-(2-ethylhexylthienyl) benzo[1,2-b:4,5-b']dithiophene (BDT) is a good electron-donating unit and has been widely used to construct efficient donor materials. 1-5 For example, the DPP-BDT-DPP typed small molecule shows a power conversion efficiency of close to 6%, which is the top values of the DPP based small-molecules.…”
Section: Introductionmentioning
confidence: 99%